Islamic landscape: the interpretation and viability of Islamic courtyard in Malaysia - Mahmood, Aisyah; Zubir, Noor Fatin Syakilla; Ab Sani, Jasasikin (KAED, IIUM, 2014)
The culture of Kuala Lumpur city dwellers is fast paced in addition to the rapid development in urban areas that contributes further to the built environment landscape. This community needs an opportunity to escape from the hustle and bustle of their daily routine to areas that promotes tranquility, greenery and humility. However, open spaces with possibilities in greenery landscape are decreasing and becoming limited. Strategies to attain such desire in an immediate outdoor space could be inculcated through the design of a courtyard. This concept is quintessential to an Islamic landscape. Fountains, pool, shade and occasional trees are also a symbolic reflection of paradise, as mentioned in the Quran. The concept of paradise garden varies according to culture but it roots on an ideal garden for people to feel the tranquility and as therapy. From this concept the Charbagh style of garden planning took root and the four-folded garden came into interpretation. This research is an attempt to investigate the possibilities and outcome for a courtyard to be part of Malaysia’s built environment. The main techniques involved are content analysis, observation and survey questionnaire. Case study is made on the courtyard of Federal Territory Mosque in Kuala Lumpur, also known as Laman Hidayah. Further studies were made at a commercial courtyards in Kuala Lumpur. 30 respondents were chosen to answer the questionnaire. Additionally, peoples’ behavioral pattern was recorded to observe the functions of the courtyards. The results suggested that an Islamic courtyard could be integrated and applied into Malaysia’s built environment providing that the correct selection of elements are arranged in relation to the surrounding. This design approach too may instill the appreciation in man towards God and His creation.